Challenges of the Elderly in Nigeria - Opeoluwa, Adeleye Paul (Magyar Gerontológia, 2024)
The elderly population in Nigeria faces a myriad of challenges as they navigate their later years. With a growing aging population, it is important to understand the life conditions and support systems available to them.